Effectiveness of Regular Online Quizzing in Increasing Class Participation and Preparation - Michael Marcell (International Journal for the Scholarship of Teaching and Learning, 2008)
Research suggests that frequent, regularly scheduled quizzing is associated with pedagogically desirable outcomes such as higher performance on exams. It was hypothesized that requiring students to complete brief scheduled online quizzes on assigned reading material before class would also result in increases in both the number of in-class questions and comments and the number of students who read the material prior to class. For each of 3 semesters, students in 1 section of introductory psychology who took time-limited, out-of-class, “open-book” WebCT quizzes on daily readings were compared to students in another section who did not take quizzes during that unit. Because each section participated in quizzing during 2 units and no quizzing during 2 units, within-section comparisons were also made. Analyses indicated that quizzing was associated with increases in both the number of student questions and comments made at the beginning of class and the number of students who reported that they came to class having read the assigned material. It was suggested that the immediate feedback provided by quizzes is particularly efficient in identifying areas of misunderstanding and in challenging students’ “illusion of knowing” the material. Spontaneous, anonymous comments on end-of-unit surveys also suggested that a primary value of online quizzing is in helping students maintain a regular reading and study schedule.